Low voltage electric system modeling and simulation - Bhuyan, Mohammed Fazlur Rahman; Likhan, Sadia Sultana (My University, 2023)
Abstract The automotive vehicle production industry has become a huge business nowadays. The vehicle market is intense and the competition is hard. Every supplier wants to give their best product and maintenance solution to the vast amount of customers who are eagerly waiting for upgrade versions and new inventions of vehicles. So, a lot of research has been going on in the vehicle industry to provide a comfortable driving and travelling experience to the end user. These research works generally comprise a lot of experi ments that require a good amount of time and money. In order to make the experiments faster, easier, and cost-effective it is a good idea to use a soft ware based model. With this software model, the initial feasibility test can be done, and then the finally passed model from the feasibility test can be developed for further practical improvement. So, in this way combination of both the software and practical model will ultimately speed up the research work and make the process more easier and cost-effective. The goal of this thesis report is to develop a software-based model for industrial and marine vehicles. In this thesis report, the low voltage auxiliary power transmission system of a basic marine vehicle (mainly used for cruise) is investigated. Such a vehicle generally contains an alternator, a battery, and loads (lights, air con ditioning system, driving control system, emergency system, etc.) The main parts of an auxiliary system like the alternator and battery are thoroughly investigated to develop an equivalent model of them that can be applicable in MATLAB SIMULINK software. After developing the model for each part they interlinked with each other. Then finally the results are compared with the practical output.